2020
DOI: 10.21273/horttech04626-20
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Healing Method for Grafted Tomato Transplants: The Effect of Light Exclusion and Substrate Temperature on Plant Survival and Growth

Abstract: The use of tomato (Solanum lycopersicum) grafting is gaining traction across the United States, but small-scale growers face the challenge of creating optimum postgrafting healing conditions. The practice of blocking light for a period of 2 to 4 days while maintaining high humidity is commonly recommended for healing grafted tomato transplants; however, research is exploring alternatives to this practice. The present study investigated a low-input healing method for grafted tomato transplants with a specific f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Therefore, the professional nurseries usually utilize healing chambers to provide a controlled environment for the healing of grafted transplants [4]. Many studies have focused on environment optimization in the healing stage for grafted transplants production in the greenhouse [5][6][7]. It is noteworthy that grafted tomato transplants have been commercially produced in the plant factory with artificial lighting (PFAL) for the advantages of high-quality, pesticidefree, and annual production [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the professional nurseries usually utilize healing chambers to provide a controlled environment for the healing of grafted transplants [4]. Many studies have focused on environment optimization in the healing stage for grafted transplants production in the greenhouse [5][6][7]. It is noteworthy that grafted tomato transplants have been commercially produced in the plant factory with artificial lighting (PFAL) for the advantages of high-quality, pesticidefree, and annual production [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the healing process of grafted seedlings, a suitable healing environment can effectively improve the healing rate and shorten the healing domestication period [3,4] . A great deal of research has shown that the time required for the connection of vascular tissue in tomato grafted seedlings can be shortened by more than 30% in a controlled environment [5][6][7] . As the source of energy and biological signals, light can influence the healing process by regulating the synthesis of the endogenous hormone, regeneration of wound-healing tissue, and connection of vascular tissue in grafted seedlings [8,9] .…”
Section: Introduction mentioning
confidence: 99%